THE GENETIC DETERMINANT ROLE IN THE DEVELOPMENT OF CARDIOVASCULAR DISORDERS IN PRETERM CHILDREN - Gonchar, M.O.; Boichenko, A.D. (World of Medicine and Biology, 2018)
In order to study the correlation between C786T polymorphic variants in the endothelial nitric oxide synthase (eNOS) gene, T58C in the mitochondrial superoxide dismutase (MnSOD2) gene and Ser49Gly in the β1-adrenergic receptor gene (ADRB1) with a risk of cardiovascular events, 120 preterm infants in the neonatal period were examined. Associated connections in a number of significant eNOS (C786T), MnSOD2 (T58C) and ADRB1 (Ser49Gly) genes polymorphisms with early development of myocardial dysfunction in preterm infants during the neonatal period have been identified. In the anamnestic study of premature babies whose mothers had the mean age of 34.1 ± 3.4 years, there was a relationship with the CC genotype (2 = 10.890; p = 0.005) of the eNOS gene polymorphism. Children whose mothers were suffering from extragenital pathology (hypertension, vegetative-vascular dysfunction, bronchial asthma, varicose veins of the lower limbs, chronic pyelonephritis, etc.), more frequently had the CC genotype (2 = 6,179; p = 0.046) of the eNOS gene polymorphism. In newborns, the relation between the CT genotype (2 = 6,552; p = 0,038) of the eNOS gene polymorphism and the presence of pathology in the female reproductive system and the problems of miscarriage of pregnancy were determined. The connection between genotypes of polymorphism of the ADRB1 gene and the presence of extragenital pathology, features of the course of pregnancy has not been established.In the neonatal period, 63.3% (38/60) of premature babies with the presence of allele C of the MnSOD2 gene polymorphism had a mean pulmonary artery pressure of 31.2 ± 2.7, (p≤0.05) mm Hg compared to 5.0% (3/60) of control group children, in which the mean pulmonary arterial pressure at the end of the neonatal period was 25.5 ± 2.0 mm Hg. In 31.7% (19/60) preterm infants, the right ventricular ejection fraction (RVEF) was 56.6 ± 1.8%, (p≤0.01) by the Simpson method, and the LV index was 0.41 ± 0.001, (p≤0.05). In 26.7% (16/60) of the examined patients being AG and GG genotypes carries of ADRB1 polymorphism, RVEF by the Simpson method was 56.7 ± 1.5% (p≤0.01), which differed from the normative indices. Based on the results obtained the following conclusions can be made:1. Associative links on a number of significant polymorphisms of eNOS (C786T), MnSOD2 (T58C) and ADRB1 (Ser49Gly) genes with early development of myocardial dysfunction in premature born children in the neonatal period have been identified.2. The presence of the ADRB1 gene GG genotype polymorphism can be considered as a predictor of the development of the hypokinetic regimen of central hemodynamics.3. Association between the CC genotype polymorphism of the eNOS gene and the contractile capacity of the left ventricle myocardium, the integral function of the left ventricle according to the Tei index has been established.4. The CC genotype of the MnSOD2 gene polymorphism is a risk factor for the formation of pulmonary hypertension.5. The risk of developing systolic-diastolic dysfunction of the right ventricle is higher in newborns with the GG genotype polymorphism of the ADRB1 gene.Thus, the results obtained by us show the possible pathogenetic role of eNOS (C786T), MnSOD2 (T58C) and ADRB1 (Ser49Gly) candidate genes polymorphism in the development of cardiohemodynamic disorders in premature infants, which has clinical significance but needs further study.
Keywords: newborn; cardiovascular disorders; polymorphism of endothelial nitric oxide synthase genes; mitochondrial superoxide dismutase; β1-adrenergic receptor gene.